2019
DOI: 10.26694/jibi.v3i2.6643
|View full text |Cite
|
Sign up to set email alerts
|

Casos Notificados de Leptospirose Humana, em Roraima, no Período 2005-2015

Abstract: O presente estudo analisou o perfil epidemiológico dos casos confirmados de leptospirose humana, notificada no estado de Roraima, entre os anos de 2005-2015, por meio da consulta em banco de dados do Sistema de Informação de Agravos de Notificação (SINAN) do Ministério da Saúde. Esta pesquisa teve por objetivo o levantamento das características epidemiológicas da infecção por Leptospira spp., em seres humanos, que permitam direcionar medidas sanitárias destinadas ao controle da doença e consequentemente a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…In relation to age group, people between 20 and 39 years old were most affected (44.7%). These results corroborate studies carried out in Alagoas, Pará and Roraima that indicated a greater incidence in males and in individuals between 20 and 39 years old (SOARES, 2017;RIBEIRO 2018;GUEDES 2021;).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In relation to age group, people between 20 and 39 years old were most affected (44.7%). These results corroborate studies carried out in Alagoas, Pará and Roraima that indicated a greater incidence in males and in individuals between 20 and 39 years old (SOARES, 2017;RIBEIRO 2018;GUEDES 2021;).…”
Section: Resultssupporting
confidence: 90%
“…Studies carried out in Paraná and Roraima demonstrated similar results (93.3% and 95.65% respectively). In the period evaluated in the state of Rondônia, the most affected area of residence was urban (57.7%), similar to what was found in the study carried out in the Federal District (SILVA 2013;RIBEIRO, 2018;SUGUIURA, 2019).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation